L’économie agro-pastorale dans le Loiret à l’âge du Fer (du Hallstatt ancien à La Tène finale) : synthèse des données carpologiques - Bénédicte Pradat (Revue Archéologique du Centre de la France)
A synthesis of carpological data on the Loiret has enabled a better understanding of food and agricultural changes in the second Iron Age. Overall, the taxonomic variety of crops both grown and harvested is high throughout the study period. Between the late Hallstatt/La Tene A and La Tene final, the changes do not take place so much in the abandonment or adoption of species, but rather in the position they occupy in terms of main, secondary or minority crop. The discovery of two rare plants, vetch and woad, also suggests trade with areas further south. Agricultural activities are not only attested through the crops, notably grain, but also the rearing of livestock (plants indicating the exploitation of meadows and evidence of fodder residues.In addition, the presence of a rather constant anthropic wooded medium could be favouredfor the contributions of the berries which it provides or to serve as hedges. Through lack of storage on site, the data on the cultivation methods are limited. Nevertheless, the passage from intensive agriculture to extensive agriculture highlighted in the north of France by V. Matterne (2001) does not seem to be as obvious in Loiret. Residues of ers have made it possible to show a practice of harvesting in the picking of this leguminous plant. In middle La Tene, a change is perceptible in the growth in the number of consumed species and a greater showing of meadow spaces. Perhaps this is related to an increase in the population and an intensification of animal husbandry.